Pengaruh Brand Ambassador Dan Sosial Media Marketing Tiktok Terhadap Keputusan Pembelian Scarlett Whitening Pada Mahasiswa Program Manajemen - St Halija; Hety Budiyanti; M.Ilham Wardhana Haeruddin; Siti Hasbiah; Ilma Wulansari Hasdiansa (Jurnal Manajemen Riset Inovasi, 2024)
ST HALIJA, 2023. "The influence of brand ambassadors and TikTok social media marketing on the decision to purchase Scarlett Whitening among Management Study Program students" Thesis of the Management Study Program, Faculty of Economics and Business, Makassar State University. Supervised by Mrs. Hety Budiyanti and Mr. M. Ilham Wardhana Haeruddin.This research aims to determine the influence of brand ambassadors and TikTok social media marketing on purchasing decisions for Scarlett Whitening. The variables studied are brand ambassador and social media marketing as independent variables and purchasing decisions as the dependent variable. The population in this study were active students of the Management Study Program at Makassar State University with a sample using purposive sampling of 100 people. This research is quantitative research which was tested using the multiple linear regression method via SPSS 23.The results of this research show that brand ambassadors partially have a positive effect of 0.115 but are not significant on purchasing decisions with a significance value of 0.229 > 0.05, social media marketing partially has a positive effect of 0.765 and is significant on purchasing decisions with a significance value of 0.000 < 0.05. Simultaneously, brand ambassadors and TikTok social media marketing influence purchasing decisions with a significance value of 0.000 < 0.05.